The Impact and Recovery of Covid-19 on the Chinese Economy: A Supply Chain Perspective as an Example - Chen, Guanxu (Transactions on Economics, Business and Management Research, 2024)
COVID-19 severely disrupted China’s supply chain, impacting global industries and prompting businesses to diversify sourcing strategies. The paper examines COVID-19’s impact on China’s supply chain, focusing on immediate disruptions and long-term adaptations towards resilience, digitalization, diversification, and sustainability. The text outlines the impact of the pandemic on China’s supply chains, highlighting immediate disruptions, medium-term adaptations, long-term transformations towards resilience and sustainability, and the accelerated digitalization in response to these challenges. The digitization of the supply chain has a profound impact on business operations and the entire industry by improving transparency, efficiency, and responsiveness, reducing costs, enhancing the resilience and flexibility of the supply chain, and promoting innovation. This also strengthens the advantages of China’s supply chain. Supply chains are evolving through resilience, digital transformation, and sustainability in response to pandemic challenges. The pandemic exposed vulnerabilities in China’s supply chain while showcasing its resilience and adaptability, solidifying its importance in global trade.